Current strategies in the management of dementia with lewy bodies and future directions based on disease pathophysiology - Daniel Erskine; John-Paul Taylor (Molecular Neurodegeneration)
Abstract Dementia with Lewy bodies (DLB) is thought to be the second most common form of dementia after Alzheimer’s disease, and is characterised by a combination of cognitive, neuropsychiatric and motor symptoms. The present review seeks to discuss current strategies for the management of DLB, and future directions for novel disease-modifying therapies. Current best practice for the clinical management of DLB is based upon therapies that target specific symptom domains due to the lack of disease-modifying therapies. Cholinesterase inhibitors are the frontline treatment for treating cognitive decline in DLB, whereas the treatment of motor symptoms remains challenging due to poor response to dopaminergic therapies and the potential for exacerbation of neuropsychiatric features. There is emerging evidence suggesting a range of further pharmacological and non-pharmacological therapies may be effective in treating specific symptom domains of DLB, but further evidence is warranted to demonstrate their efficacy. A key challenge in the treatment of DLB is incomplete understanding of disease pathophysiology, which has limited attempts to develop disease-modifying therapies. In the present article, we discuss the multi-faceted nature of DLB neuropathology, from Lewy body pathology to mitochondrial dysfunction, and discuss therapies in development that target particular aspects of DLB neuropathology. In particular, we highlight antibody-based therapies to attenuate protein aggregation, compounds that enhance the generation of cellular energy and autophagy-enhancing agents as particular areas of promise. Furthermore, we discuss how optimal strategies for disease modification will be centred on agents that treat DLB neuropathology more holistically, and will be underpinned by a more complete understanding of the pathogenic events that underlie the full spectrum of pathological changes observed in the DLB brain.